Treatment of African children with severe malaria - towards evidence-informed clinical practice using GRADE. - Musila, N; Opiyo, N; English, M (BioMed Central, 2011)
BACKGROUND: Severe malaria is a major contributor of deaths in African children up to five years of age. One valuable tool to support health workers in the management of diseases is clinical practice guidelines (CPGs) developed using robust methods. A critical assessment of the World Health Organization (WHO) and Kenyan paediatric malaria treatment guidelines with quinine was undertaken, with a focus on the quality of the evidence and transparency of the shift from evidence to recommendations. METHODS: Systematic reviews of the literature were conducted using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) tool to appraise included studies. The findings were used to evaluate the WHO and Kenyan recommendations for the management of severe childhood malaria. RESULTS: The WHO 2010 malaria guidance on severe malaria in children, which informed the Kenyan guidelines, only evaluated the evidence on one topic on paediatric care using the GRADE tool. Using the GRADE tool, this work explicitly demonstrated that despite the established use of quinine in the management of paediatric cases of severe malaria for decades, low or very low quality evidence of important outcomes, but not critical outcomes such as mortality, have informed national and international guidance on the paediatric quinine dosing, route of administration and adverse effects. CONCLUSIONS: Despite the foreseeable shift to artesunate as the primary drug for treatment of severe childhood malaria, the findings reported here reflect that the particulars of quinine therapeutics for the management of severe malaria in African children have historically been a neglected research priority. This work supports the application of the GRADE tool to make transparent recommendations and to inform advocacy efforts for a greater research focus in priority areas in paediatric care in Africa and other low-income settings.